A distinctive fraction of alkaline phosphatase in health and disease. Issue 5 (September 1966) - Newton, M. A.
Abstract : An electrophoretic fraction of plasma alkaline phosphatase, which migrates more slowly than the main fraction, was present in one fifth of normal subjects, and in some patients with parenchymal liver disease. It was absent in patients with bone disease, uncomplicated biliary obstruction, and hepatic metastases. The electrophoretic and inhibition properties of this slow band were similar to those of intestinal phosphatase, and its significance is discussed. In a patient with hypophosphatasia this fraction was apparently not decreased.